2008
DOI: 10.1183/09031936.00018908
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted mechanisms in COPD: inflammation, immunity, and tissue repair and destruction

Abstract: Chronic obstructive pulmonary disease is a leading global cause of morbidity and mortality that is characterised by inexorable deterioration of small airways obstruction with emphysema associated with cellular inflammation and structural remodelling. Other features include apoptosis as well as proliferation of cells, and both tissue repair and lack of tissue repair.Metalloprotease release, together with that of apoptotic factors, may underlie the emphysema, and, conversely, fibrosis of the small airways may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
435
2
28

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(473 citation statements)
references
References 304 publications
(319 reference statements)
8
435
2
28
Order By: Relevance
“…In addition, we confirmed that the% predicted post bronchodilator FEV1 was inversely correlated to the proportion of neutrophils [23,25,35]. It suggests that neutrophilic inflammation is an important factor in the pathogenesis of irreversible airflow limitation in COPD [5]. On the other hand, high sputum neutrophil count may reflect constant activation of local innate immunity in response to bacterial colonization developing in remodelled and altered airways [20].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, we confirmed that the% predicted post bronchodilator FEV1 was inversely correlated to the proportion of neutrophils [23,25,35]. It suggests that neutrophilic inflammation is an important factor in the pathogenesis of irreversible airflow limitation in COPD [5]. On the other hand, high sputum neutrophil count may reflect constant activation of local innate immunity in response to bacterial colonization developing in remodelled and altered airways [20].…”
Section: Discussionsupporting
confidence: 70%
“…Chronic inflammation in COPD is orchestrated by the activity of cytokines and chemokines, of which many can be detected at increased levels in the circulation of patients [5,23]. In stimulation experiments using endothelial cells that, in vivo, reflect the first responders of the lungs to these proinflammatory signals, we found that IL-1β and TNFα significantly induced the levels of miR-223 in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
“…These factors, among other mechanisms, lead to infiltration of the airway epithelium with inflammatory cells, chronic bronchial inflammation and consecutive tissue destruction [5].…”
Section: Introductionmentioning
confidence: 99%
“…O acúmulo de macrófagos nas paredes das vias aéreas e no parênquima pulmonar dos tabagistas que desenvolvem DPOC pode ser explicado tanto pelo prolongamento do tempo de vida da célula no pulmão como pelo aumento do recrutamento de monócitos (seu precursor) da circulação 13 . Alguns trabalhos sugerem que a participação dos macrófagos na patogênese da DPOC tem relação com a sua capacidade de produzir enzimas metaloproteases (MMP) como a MMP-1, MMP-9 e MMP-12 14,15,16,17 . Acredita-se que as metaloproteases sejam capazes de degradar proteínas de forma semelhante às enzimas neutrofílicas 14 e recrutar células inflamatórias da circulação, facilitando sua infiltração nos tecidos lesados 15 .…”
Section: Macrófagosunclassified
“…Alguns trabalhos sugerem que a participação dos macrófagos na patogênese da DPOC tem relação com a sua capacidade de produzir enzimas metaloproteases (MMP) como a MMP-1, MMP-9 e MMP-12 14,15,16,17 . Acredita-se que as metaloproteases sejam capazes de degradar proteínas de forma semelhante às enzimas neutrofílicas 14 e recrutar células inflamatórias da circulação, facilitando sua infiltração nos tecidos lesados 15 . Macró-fagos recolhidos do lavado broncoalveolar (LBA) de pacientes com DPOC apresentam aumento da expressão de receptores para MMP-1 e MMP-9 16 , enquanto que tanto camundongos com deficiência de MMP-12 16 quanto o uso de inibidores de MMP em cobaias 18 apresentam efeito protetor à exposição à fumaça de cigarro.…”
Section: Macrófagosunclassified